From ynamides to highly substituted benzo[b]furans: gold(I)-catalyzed 5-endo-dig-cyclization/rearrangement of alkylic oxonium intermediates - Blanco Jaimes, Maria Camila; Claus, Vanessa; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2013)
A series of arylynamides with alkyloxy groups at the ortho position of the aryl group was prepared through a short alkylation/cross-coupling/amidation sequence. The gold-catalyzed conversion of these substrates combined both CO and CC formation steps, thus providing benzofurans with amine functionalities at the 2-position and alkyl groups at the 3-position. Cross-over experiments showed that the alkyl-migration step was an intermolecular process. X-ray crystal-structure analysis of two of the products supported our structural assignment. In some cases, the corresponding benzofurans without the alkyl group at the 3-position were obtained as side-products, which were formed through a competing protodeauration process.
Gesehen am 30.04.2021